The quadratic cannot be factored in terms of integers, so the final answer has to be the same as the original expression.
Go to www.quickmath.com and click on the Quadratics link along the left. Plug in your formula and see what I'm talking about. BTW you will LOVE the Quickmath site. They even walk you through the solution.
2x^2-3x-4
3 +- sqrt of 9 - (4*-8) =
3 +- sqrt of (9+32) / 4=
3 +- sqrt of (41) / 4
These roots are irrational, the quadratic cannot be factored in terms of integers.
2007-03-23 03:22:23
·
answer #1
·
answered by Cambion Chadeauwaulker 4
·
1⤊
0⤋
2x^2 - 3x - 4 = 0
Using formula for roots of a quadratic equation
x = 3 +/- sqrt(9+32)/2
x = 3/2 + sqrt(41)/2 or x = 3/2 - sqrt(41)/2
Answer x = (-4.9031,7.9031)
2007-03-23 10:21:22
·
answer #2
·
answered by Nishit V 3
·
0⤊
1⤋
Quadratic Equation
x = - b ± âb² - 4ac / 2a
x = - (- 3) ± â(-3)² - 4(2)(- 4) / 2(2)
x = 3 ± â9 - (- 32) / 4
x = 3 ± â9 + 32 / 4
x = 3 ± â41 / 4
x = 3 ± 6.403124237 / 4
- - - - - - - - - -
Solving for +
x = 3 + 6.403124237 / 4
x = 9.403124237 / 4
x = 2.350781059
- - - - - - -
Solving for -
x = 3 - 6403124237 / 4
x = -3.403124237 / 4
x = - 0.850781059
- - - - - - -s-
2007-03-23 10:49:26
·
answer #3
·
answered by SAMUEL D 7
·
0⤊
1⤋
2x^2 - 3x - 4 = 0
a b c
use the formula for quadratic equations ( x=-b +or- root of b^2-4ac/2a)
x= --3+or- [root of (-3)^2-4(2)(-4)]/2(2)
x=3+or- [root of 9+32]/4
x=3+or- [root of 41]/4
or you can simplify it to decimal form
x= (-0.64921894... , 2.350781059...)
round to nearest 1000th
x= about (-0.649, 2.351)
Answer x = (-4.9031,7.9031)
Hope that helps!
2007-03-23 10:35:53
·
answer #4
·
answered by BlueSmiley 3
·
0⤊
1⤋
Use the formular for solving quadratic equation.
x = (3+sq root (9+32))/4 or
x = (3-sq root (9+32))/4
Pse compute the answer yourself.
2007-03-23 10:22:01
·
answer #5
·
answered by Kenche L 2
·
1⤊
1⤋
You have to use the quadratic formula:
x=-b屉b^2-4ac/2a
a=2,b=-3,c=-4
x=(3屉(-3)^2-4(2*-4))/2(2)
x=(3屉9+32)/4
x=(3屉41)/4
x=-.85 or 2.35
2007-03-23 11:19:51
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
2x² - 3x - 4 = 0
x = [3 ± â(9 + 32)] / 4
x = [ 3 ± â(41) ] / 4
x = 2.35, - 0.85
2007-03-23 10:24:48
·
answer #7
·
answered by Como 7
·
1⤊
1⤋
I believe that it is no solution... i can't get it to factor
2007-03-23 10:25:30
·
answer #8
·
answered by absolution0408 2
·
1⤊
1⤋
this is a wrong equation.
2007-03-23 10:24:06
·
answer #9
·
answered by creagrouption 1
·
0⤊
2⤋